ADVERSITY DI MASA PANDEMI COVID-19 SISWA SEKOLAH DASAR PADA PEMBELAJARAN MATA PELAJARAN PENDIDIKAN AGAMA KRISTEN - Yuel Sumarno; Syanti Dewi; Jannes Eduard Sirait; Agusti Layung Vandiila Putri (Edukasi : Jurnal Pendidikan Agama Kristen, 2022)
This study aims to explore the forms of adversity, adaptation strategies, and the role of teachers in Christian Religious Education for elementary school students during the COVID-19 pandemic. A qualitative case study approach was employed, with data collected through in-depth interviews, observations, and document analysis. The findings reveal that students encountered various types of adversity, including limited access to learning devices and internet connectivity, difficulties adapting to online learning, psychosocial challenges, and the loss of spiritual experiences typically gained in the classroom. Nevertheless, some students demonstrated resilience supported by family involvement, personal creativity, and teachers who acted as both academic facilitators and spiritual mentors. The study highlights the crucial role of Christian Education teachers in designing creative, interactive, and contextual learning while providing emotional and spiritual support to students. It recommends strengthening teachers’ capacity in digital literacy, online pedagogy, and psychosocial support to ensure that Christian Religious Education remains meaningful and relevant during crisis situations.